The Use of Improvisations Technique to Improve the Speaking Ability of EFL Students - Fauzan, Umar (IAIN Samarinda, 2014)
The objective of the study was to implement the improvisations technique to improve the student’s speaking ability. In conducting the research, there were two components expected to be improved, they were improving the students’ speaking score and increasing the quality of classroom atmosphere of teaching speaking. This study employed the collaborative classroom action research and it was done in two cycles. Each cycle consisted of four stages: (1) planning, (2) action, (3) observation, and (4) reflection. There were five meetings in each cycle; four meetings for the implementation of improvisations in the teaching of speaking and one meeting for conducting speaking test. The instruments used to collect the data were: (1) observation checklist, (2) field-note, (3) a score sheet, and (4) a questionnaire. The result of the research showed that the criteria of success had been reached. There were two aspects determined as the success criteria of the implementation of improvisations in the teaching of speaking; score improvement and classroom atmosphere. The result of speaking test presented that the students had made some progress, the average scores raised from 2.72 in the pre-test, 3.09 in cycle 1 and 3.76 in cycle 2. These scores indicated an increasing ability from being ‘fair’ to being ‘good’. The classroom atmosphere were also increasing positively; the students were actively involved in the teaching and learning process, indicated by 64% participated in cycle 1 and 73.79% participated in cycle 2. The students were also highly motivated in joining the teaching learning process. They cooperated, asked, responded, and expressed spontaneously.